Selection and Cultivation of Microalgae for CO2 Biofixation. Issue 1 (February 2021) - Widayat,; Suzery, M; Satriadi, H; Wahyudi,; Philia, J
Abstract: Climate change has become the main focus of the world which caused various negative impacts throughout the earth. Carbon dioxide is one of the greenhouse gases that effect on climate change and environmental pollution. One of the promising opportunities to reduce CO2 emissions in the atmosphere is bio fixation by microalgae. Many species of microalgae have the ability to capture carbon dioxide as its carbon source for the photosynthetic process. This research aimed to cultivate many species of microalgae in the carbon dioxide incubator and study its CO2 bio-fixation capability. Microscopic analysis was occurred to identify microalgae morphology. The optical density measured representing growth rate of microalgae. Tetraselmis sp . and Navicula sp. are suitable for CO2 biofixaton due to the good adaptation to the existence of CO2 in the medium.